1982
DOI: 10.1007/bf00848411
|View full text |Cite
|
Sign up to set email alerts
|

The temporal and spatial relationships between cortical contraction, sperm trail formation, and pronuclear migration in fertilizedXenopus eggs

Abstract: The cortical contraction begins 4 min after insemination and one minute after prick activation. During the next 4 min, the pigment margin moves 15 degrees toward the animal pole. The cortex then relaxes to the prefertilization level over the next 10 min. Contrary to earlier estimations, the cortical contraction occurs during the same time span as the wave of cortical granule exocytosis. We suggest that the two events may result from a common stimulus. The sperm trail (ST) forms during the relaxation of the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…Pigment concentrates about the SEP, marking the future ventral side, and making axis manipulation possible in early stages [10,13,58,59,107]. The path of the migrating male pronucleus (plate I, A) is marked by pigment granules, drawn into the cytoplasm from the egg surface as the sperm moves inward (NT 0.17-0.61) [6][7][8][9][10]13]. The female pronucleus moves down from the animal pole, probably soon coming under influence of the spermaster [108].…”
Section: Morphological Phenomena Started By Sperm Penetrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Pigment concentrates about the SEP, marking the future ventral side, and making axis manipulation possible in early stages [10,13,58,59,107]. The path of the migrating male pronucleus (plate I, A) is marked by pigment granules, drawn into the cytoplasm from the egg surface as the sperm moves inward (NT 0.17-0.61) [6][7][8][9][10]13]. The female pronucleus moves down from the animal pole, probably soon coming under influence of the spermaster [108].…”
Section: Morphological Phenomena Started By Sperm Penetrationmentioning
confidence: 99%
“…As a consequence the two animal-dorsal blastomeres are smaller in most 8-cell Xenopus embryos [26]. During the first cell cycle two main independent microtubular entities develop: (1) the spermaster, initiated in the animal hemisphere by the sperm centriole [6,7,9], and (2) an array of parallel MT in the subcortical cytoplasm of the vegetal hemisphere about half-way through the first cleavage [82a, 107, 110]. In 6 mm paraffin sections of Bouin d'Hollande-fixed [77, 85, 86, 96a] Xenopus eggs we analyzed the three-dimensional distribution of tubulin with a modified peroxidase-anti-peroxidase (PAP) procedure [82, 82a].…”
Section: Morphological Phenomena Started By Sperm Penetrationmentioning
confidence: 99%
See 1 more Smart Citation
“…For X. laevis , studies have indicated a signifi cantly higher number of spermatozoa binding to the animal hemisphere ( 35,36 ). The fi rst visible sign of egg activation is the movement of pigment granules toward the animal pole (termed cortical contraction), which occurs approximately 4 min after fertilization ( 37 ). Our aim was to investigate the biological phenomenon on the surface of the egg shortly after the fertilization.…”
Section: Monitoring the Lipid Distribution On The Animal Hemisphere Omentioning
confidence: 99%
“…During fertilization of most species, the sperm entry into the egg cytoplasm, the exocytosis of cortical granules, and the meeting of sperm and egg pronuclei all appear to require actin filaments (Stewart-Savage and Grey, 1982;reviewed in Vaquier, 1981).…”
Section: Fertilization and Early Cleavagementioning
confidence: 99%